Shimon Samet and the Gap in the Story - YEHOSHUA (SHUKI) ECKER (Autobiografia, 2020)
This article offers a close reading of personal memoirs about coming of age in Żółkiew in Eastern Galicia and about transitions on the way to immigration to Mandatory Palestine before WWII. It focuses on gaps in the fragmentary autobiographical texts written by Shimon Samet, a native of the town, who became an accomplished professional journalist in Israel, and reconstructs missing pieces of narrative about Samet’s brother and about the Zionist micro universe of transition and training sites in Galicia of the early 1920’s. It points to significant explanatory possibilities gained by identifying such gaps in personal and commemorative narratives.